Gendered Code-Switching and Social Identity Construction among Bilingual Speakers in Urban Multilingual Communities: A Case Study of the University of Jhang - Muhammad Shahrugh Bukhari; Dr. Muhammad Siddique (ACADEMIA International Journal for Social Sciences, 2025)
This paper explores gendered code-switching and the construction of social identity in the context of Bilingual speakers in an urban multilingual university through the case study of the University of Jhang. In multilingual countries such as Pakistan, there is often a tendency by the bilingual to switch languages when engaging in daily conversation. This study aims to discuss the patterns of code-switching, discover gender-specific variations in the choice of language, and find out how code-switching helps to develop the social identity within the university environment. The context of the research is based on sociolinguistic studies whereby code-switching is regarded as a relevant social behaviour, and not a sign of linguistic ineptitude. The research design is a qualitative dominant mixed-method study in a case study. The theoretical framework is based on the Interactional Sociolinguistics and Social Constructionist theories of identity, in reference to the idea of contextualization cues as proposed by Gumperz and identity framework suggested by Bucholtz and Hall. We were able to collect data by the use of audio recordings of classroom discussions, peer discussions, informal campus conversation, and semi-structured interviews. The sampling technique employed was purposive and a sample of 25 undergraduate and postgraduate bilingual students was selected. The results indicate that intra-sentential, inter-sentential and tag switching are contextually systematically utilized. Gender also determines the rate and purpose of code-switching, where the female speakers prefer relational and expressive purposes whereas male speakers apply strategic switching in official situations. Code-switching becomes the major asset in building academic identity, modernity, politeness, authority, and group belonging. The research proposes the acknowledgement of code-switching as an authentic communicative and pedagogical tool in multilingual universities campuses.